Numerical simulation and application experiment of the spontaneous combustion tendency of a coal stockpile covered with pulverized coal. (21st October 2019) - Chu, Ruizhi; Wang, Minglei; Meng, Xianliang; Liu, Peng; Liu, Zhenyi; Wu, Jiaxin; Yang, Deguang; Chen, Hui; Bai, Lei
Abstract: In this paper, we developed a new method for preventing the spontaneous combustion of a coal stockpile covered by pulverized coal. This technique is based on the numerical‐simulation analysis of endothermic/exothermic balance in coal stockpile. Depth and height are confirmed to be the main factors influencing the endothermic/exothermic balance in coal stockpiles and the hot‐spot region is easily formed at a coal stockpile height of 1‐1.5 m and a depth of 2‐3 m, where there is the highest tendency for spontaneous combustion. The numerical simulation and the 120‐day application test both confirm that the diffusion process of oxidation can be prevented and the coal oxidation reaction can be hindered by covering the surface of the hot region with pulverized coal. As a result, the coal spontaneous combustion is prevented effectively. Abstract : Trend of temperature and oxygen concentration after being covered with pulverized coal.